Dramatising the shock of the new: using Arts-based embodied pedagogies to teach life skills. Issue 5 (3rd September 2021) - Robbie, Sheila; Warren, Bernie
ABSTRACT: The digital economy and the global pandemic, together with the effects of climate change, have taken a human toll affecting the pace of everyday life, creating an exponential increase in anxiety and stress related diseases. Today's complex, globalised world creates a need to challenge and reconceptualise educational priorities. In an increasingly polarised world of beliefs and values, with a rise in populism and nationalism, empathy is essential. In order to function successfully, one needs to know who people are, and the whys and wherefores of their actions and beliefs. This article focuses on how the Arts and humanities can teach a new generation of life skills necessitated by our globalised society and the socio-political aspects of immigration. It discusses how embodied pedagogies help develop self-awareness, emotional regulation and affective empathy and reduce stress. The authors present Arts-based pedagogies and educational strategies that bring history, cultures and beliefs alive and help counteract hatred, tribalism and racism and the illusion of 'us and them.' The article examines what these changes in pedagogy can offer to the discourse, both in the need to keep body/mind healthy and acquisition of new skills necessary for adapting to a changing global environment and cultural /political landscapes.